2008
DOI: 10.4161/cc.7.9.5806
|View full text |Cite
|
Sign up to set email alerts
|

Paternal cranial irradiation induces distant bystander DNA damage in the germline and leads to epigenetic alterations in the offspring

Abstract: It is now well accepted that parental whole body irradiation causes transgenerational genome and epigenome instability in the offspring. The majority of human exposures to radiation, such as therapeutic and diagnostic irradiation, are localized and focused. The potential of localized body-part exposures to affect the germline and thus induce deleterious changes in the progeny has not been studied. To investigate whether or not the paternal cranial irradiation can exert deleterious changes in the protected germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…DNA strand breaks were measured using the modification of a random oligonucleotide primed synthesis (ROPS) assay. 17 Using this assay, we found that radiation exposure induced a significant 2.2 fold increase in the level of DNA strand breaks in testes of exposed animals ( Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…DNA strand breaks were measured using the modification of a random oligonucleotide primed synthesis (ROPS) assay. 17 Using this assay, we found that radiation exposure induced a significant 2.2 fold increase in the level of DNA strand breaks in testes of exposed animals ( Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of γH2AX foci, a direct indicator of DNA damage, was assayed using immunohistochemistry. 17 Analysis revealed that radiation exposure led to a noticeable increase in γH2AX foci in exposed testes (Fig. 2B).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations